Physiological differences in cardiopulmonary exercise testing between children and adults - Valentina Papic; Romina Ledergerber; Ralf Roth; Raphael Knaier (Current Issues in Sport Science)
Purpose: This study examines age- and sex-related physiological differences in cardiopulmonary exercise testing (CPET) between children and adults, focusing on ventilatory thresholds (VT) and oxygen uptake efficiency slope and plateau (OUES; OUEP).